Biliary Cystadenoma: An Unusual Cause of Acute Pancreatitis and Indication for Mesohepatectomy - Bilal Munir; Michael Meschino; Ashley Mercado; Roberto Hernandez-Alejandro (Case Reports in Gastrointestinal Medicine)
The classic presentation of cystic hepatobiliary lesions is usually nonspecific and often identified incidentally. Here we describe the case of a patient presenting with acute pancreatitis resulting from a large centrally located biliary cystadenoma compressing the pancreas. Determination of the origin of the cystic lesion was difficult on imaging studies. Due to the difficult location of the lesion, a complete surgical resection was achieved with mesohepatectomy and the suspected diagnosis confirmed by pathology. The patient continues to do well 2 years post-op with no signs of recurrence.